Mechanotranduction Pathways in the Regulation of Mitochondrial Homeostasis in Cardiomyocytes - Liao, Hongyu; Qi, Yan; Ye, Yida; Yue, Peng; Zhang, Donghui; Li, Yifei (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are one of the most important organelles in cardiomyocytes. Mitochondrial homeostasis is necessary for the maintenance of normal heart function. Mitochondria perform four major biological processes in cardiomyocytes: mitochondrial dynamics, metabolic regulation, Ca2+ handling, and redox generation. Additionally, the cardiovascular system is quite sensitive in responding to changes in mechanical stress from internal and external environments. Several mechanotransduction pathways are involved in regulating the physiological and pathophysiological status of cardiomyocytes. Typically, the extracellular matrix generates a stress loading gradient, which can be sensed by sensors located in cellular membranes, including biophysical and biochemical sensors. In subsequent stages, stress stimulation would regulate the transcription of mitochondrial related genes through intracellular transduction pathways. Emerging evidence reveals that mechanotransduction pathways have greatly impacted the regulation of mitochondrial homeostasis. Excessive mechanical stress loading contributes to the impair mitochondrial function, leading to cardiac disorder. Therefore, the concept of restoring mitochondrial function by shutting down the excessive mechanotransduction pathways is a promising therapeutic strategy for cardiovascular diseases. Recently, viral and non-viral protocols have shown potentials in application of gene therapy. This review examines the biological process of mechanotransduction pathways in regulating mitochondrial function in response to mechanical stress during the development of cardiomyopathy and heart failure. We also summarize gene therapy delivery protocols to explore treatments based on mechanical stress induced mitochondrial dysfunction, to provide new integrative insights into cardiovascular diseases.